2019
DOI: 10.1002/pros.23796
|View full text |Cite
|
Sign up to set email alerts
|

Dietary palmitate cooperates with Src kinase to promote prostate tumor progression

Abstract: Numerous genetic alterations have been identified during prostate cancer progression. The influence of environmental factors, particularly the diet, on the acceleration of tumor progression is largely unknown. Expression levels and/or activity of Src kinase are highly elevated in numerous cancers including advanced stages of prostate cancer. In this study, we demonstrate that high-fat diets (HFDs) promoted pathological transformation mediated by the synergy of Src and androgen receptor in vivo. Additionally, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Our study focused on the effect of PA, one of the main components of lipids, on PCA development. Earlier articles indicated that PA could increase invasiveness of cancer cells [17,36,37]. Our research showed that PA induced tumor growth in a PCA xenotransplantation model and accelerated PCA progression in c-Myc T mice.…”
Section: Discussionsupporting
confidence: 54%
“…Our study focused on the effect of PA, one of the main components of lipids, on PCA development. Earlier articles indicated that PA could increase invasiveness of cancer cells [17,36,37]. Our research showed that PA induced tumor growth in a PCA xenotransplantation model and accelerated PCA progression in c-Myc T mice.…”
Section: Discussionsupporting
confidence: 54%
“…However, it was not conclusive that the inhibition was due to metabolic competition or competitive uptake. With PA, also a FA that induces metastatic effects of PC-3 cells [42,43], it is hypothesised that the uptake could be inhibited by omega-3 FAs such as DHA and EPA. The Raman results acquired here suggest that the omega-3 FAs do inhibit the uptake of PA by the PC-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, further analysis revealed that tumour incidence (involving several tumour sites in mice) was positively associated with total caloric intake, regardless of the level of dietary fat [95]. In addition, in isocaloric diets, it is the fat type that matters in tumour promotion, and progression [96][97][98], as the impact of different FAs on signalling pathways involved in cell proliferation varies [99,100]. Furthermore, interpolating animal data is tricky, in part because of differences in metabolism, in part due to factors which, unlike in vivo studies, cannot be controlled in full in human studies (e.g., total caloric intake, macronutrient, and micronutrient composition, lifestyle factors, etc.…”
Section: Dietary Fat and Cancer Riskmentioning
confidence: 99%
“…A diet high in PA enhanced the proliferation of prostate cancer xenografts in comparison with a diet high in unsaturated fat. PA increased the level of Src kinase and Src-mediated downstream signalling, including MAPK activation, and also enhanced Src-dependent mitochondrial β-oxidation [98]. PA increased the invasiveness of AsPC-1 pancreatic cancer cells via the TLR-4/ROS/NF-κB/matrix metalloproteinase-9 (MMP-9) signalling pathway [148] and promoted metastasis in several human oral carcinoma cell lines expressing high levels of cluster of differentiation 36 (CD36) [149].…”
Section: The Role Of Sfas In Signalling Pathways Involved In Cancer Palmitic Acidmentioning
confidence: 99%